Efficiency of Bed Utilization at Medan Adventist Hospital in 2025 - Julvian Zebua, Bernard; Simbolon, Pomarida; Ginting, Arjuna (LPPM Universitas Mohammad Husni Thamrin, 2025)
Hospitals are health care institutions that provide comprehensive individual health services that provide inpatient, outpatient, and emergency services. Hospitals are also places to organize health efforts, namely every activity to maintain and improve health and aim to realize optimal health levels for the community. The efficiency of bed use is an indicator that underlies the performance of all hospitals. Efficiency can be used to allocate existing resources to achieve targets more quickly and optimally. BOR is the utilization of beds in a certain time unit. This indicator provides an overview of the high and low levels of bed utilization in hospitals. To Identify the Efficiency of Bed Use in Adventist Hospital. The results of the study on BOR, the BOR value is not ideal as much as 7 (10.7%), the ideal value of BOR obtained a value of 51 (60.75%), the value above the ideal number of BOR obtained a value of 24 (28.6). AVLOS is not ideal 100%, TOI is not ideal 100%. The BTO value shows a value above the ideal number. The value above the ideal number of BTO is 84%. The instrument used in this study uses an observation sheet. The data analysis used in this study was univariate. It is hoped that Medan Advent Hospital will further improve the efficiency of bed utilization in 2025 to ensure proper patient care.